Designing and implementing an SWMM-based web service framework to provide decision support for real-time urban stormwater management. (January 2021) - Zeng, Zhiqiang; Yuan, Xiaohui; Liang, Ji; Li, Yuhong
Abstract: Storm Water Management Model (SWMM), a hydrodynamic rainfall-runoff and urban drainage simulation model, is widely applied in planning, analysis, and design. It is worth mentioning that the hydrological and hydrodynamic simulation functions of SWMM can also provide decision support for real-time urban stormwater management. However, it remains challenging to directly apply traditional SWMM to real-time urban stormwater management based on web technology. Here we designed and implemented a web service framework based on SWMM (WEB-SWMM), which can provide real-time computing services for urban water management. To test the functionality, efficiency, and stability of the WEB-SWMM, WEB-SWMM was applied to an urban area in China. Test results show that WEB-SWMM could provide real-time computing services stably, quickly, and accurately. In general, the implementation of WEB-SWMM enables traditional SWMM to be quickly and efficiently applied in real-time urban stormwater management. What is more, the web-based hydrological model framework proposed in this paper also applicable to most existing hydrological models. Highlights: The real-time simulation of SWMM is implemented. WEB-SWMM can provide real-time computing services for urban stormwater management. WEB-SWMM can provide web services and exchange data with other applications. The core four tasks and four modules guarantee the regular running of WEB-SWMM. The framework can be installed and deployed across platforms.